Efficient polyester resin synthesis using microwave heating with scale-up from 50 mL to 5 L - Hargreaves, George William (2017)
Polyesters are a vital part of modern day life, with a plethora of different uses such as clothing, coatings, biomedical engineers, drug encapsulation and much more. This means that the synthesis of these products from the raw materials is vital and investigating a way to increase the synthesis efficiency is an important topic of research. The work discussed within this thesis aims to assess in depth the impact which microwave energy has on a melt polycondensation system, suggesting that implementing a microwave heating into the polycondensation, there is potential to reduce production times and potentially increase product molecular weights. This is explained through a discussion about catalytic mechanisms and selective microwave heating. This led to the design and commissioning of a 5 L scale-up vessel with hybrid conventional and microwave heating capabilities to show that these technologies can be scaled to an industrially meaningful scale.